-(3x+2)=-19x+62

Simple and best practice solution for -(3x+2)=-19x+62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x+2)=-19x+62 equation:


Simplifying
-1(3x + 2) = -19x + 62

Reorder the terms:
-1(2 + 3x) = -19x + 62
(2 * -1 + 3x * -1) = -19x + 62
(-2 + -3x) = -19x + 62

Reorder the terms:
-2 + -3x = 62 + -19x

Solving
-2 + -3x = 62 + -19x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '19x' to each side of the equation.
-2 + -3x + 19x = 62 + -19x + 19x

Combine like terms: -3x + 19x = 16x
-2 + 16x = 62 + -19x + 19x

Combine like terms: -19x + 19x = 0
-2 + 16x = 62 + 0
-2 + 16x = 62

Add '2' to each side of the equation.
-2 + 2 + 16x = 62 + 2

Combine like terms: -2 + 2 = 0
0 + 16x = 62 + 2
16x = 62 + 2

Combine like terms: 62 + 2 = 64
16x = 64

Divide each side by '16'.
x = 4

Simplifying
x = 4

See similar equations:

| 25.748=2*3.14*r^2+2*3.14*r*3.1 | | 5a+10b=450 | | 453.6672=2*3.14*r^2+2*3.14*r*13 | | 5b+10a=450 | | -1-0.28v=2 | | 5*26=x | | -5+3(6-x)=1 | | 4x*3=99+x | | 20x=.6 | | 10a+5b=450 | | -2(6p-5)+2p=8p-8 | | 2(0,3x-1)-0,6=4+0,1x | | 8+10y=9y-6 | | -16t^2+57=0 | | 17x=6x-22 | | 138-4x=32x+22 | | 10.5=3b-12.5 | | 4x+2x+96-22=88+4x | | 6-3x-5x-1=10 | | 4(3x-44)=4(2x-10) | | 4x^4-17x^2+18=0 | | 5x*3+17=69+2x | | -2(3x-4)+12=8 | | -16t^2+7.85t+57=0 | | 4-x-2-x=x | | 5x^2+4xy-12y^2=0 | | 4-x-2+x=x | | 189.028=2*3.14*r^2+2*3.14*r*2.7 | | 6a+8b=1500 | | 3t-6=2t+2 | | -3x+8=-1 | | (3x*7)=21 |

Equations solver categories